Fast qualitative two-dimensional mapping of ultrasound fields with acoustic cavitation-enhanced ultrasound imaging - Burgess, Mark T. (J Acoust Soc Am, 2019)
Characterization of ultrasound fields is a routine procedure for both diagnostic and therapeutic ultrasound. Quantitative field mapping with a calibrated hydrophone and multi-axis positioning system can be difficult and time consuming. In this study, the use of acoustic cavitation field mapping as a qualitative surrogate to acoustic pressure field mapping, albeit without acoustic pressure values is demonstrated. This technique allows for fast qualitative mapping of ultrasound fields and thereby functionality of the corresponding transducers, in a matter of seconds. In addition, this technique could be used to rapidly image in vivo acoustic cavitation fields during therapeutic ultrasound applications.